1988
DOI: 10.1073/pnas.85.6.1740
|View full text |Cite
|
Sign up to set email alerts
|

An endogenous activator of the Ca2+-dependent proteinase of human neutrophils that increases its affinity for Ca2+.

Abstract: An endogenous activator of the Ca2l-depen~dent proteinase (calpain) has been identified in human neutrophils, In the presence of the activator, the affinity of calpain for Ca2+ is increased by >100-fold and maximum catalytic activity is observed with Ca2" concentration below 1 ,uM. The activator is a heat-stable protein having an apparent molecular mass of -40 kDa. It appears to be associated with the cytoskeletal fraction of human neutrophils. Neutrophils also contain an endogenous cytosolic calpain inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…The original hypothesis was initially proposed on two bases (see the Introduction) : (i) an attempt has been made to find a molecular function for sequences selected through a statistical analysis of primary structures of stable and unstable proteins ; and (ii) taking into account that the requirement of calcium for activating calpains in itro is one to three orders of magnitude (depending on the type of calpain) higher than physiological intracellular calcium concentrations, it has been suggested that PEST motifs might chelate calcium and thus activate calpains at the substrate level. However, it has more recently been reported that both lipid [40,41] and protein [42][43][44][45] activators increase dramatically (up to 100-fold) the affinity of calpains for calcium. This thus makes unlikely the hypothesis that the concentration of calcium at the level of substrates, through chelation by PEST motifs, is a prerequisite for cleavage by calpains.…”
Section: Discussionmentioning
confidence: 99%
“…The original hypothesis was initially proposed on two bases (see the Introduction) : (i) an attempt has been made to find a molecular function for sequences selected through a statistical analysis of primary structures of stable and unstable proteins ; and (ii) taking into account that the requirement of calcium for activating calpains in itro is one to three orders of magnitude (depending on the type of calpain) higher than physiological intracellular calcium concentrations, it has been suggested that PEST motifs might chelate calcium and thus activate calpains at the substrate level. However, it has more recently been reported that both lipid [40,41] and protein [42][43][44][45] activators increase dramatically (up to 100-fold) the affinity of calpains for calcium. This thus makes unlikely the hypothesis that the concentration of calcium at the level of substrates, through chelation by PEST motifs, is a prerequisite for cleavage by calpains.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that isovalerylcarnitine reduced the Ca 2ϩ concentration required for maximal proteolytic activity of m-calpain to Ͻ10 M and increased its specific activity by 1.5-fold, but did not affect either the Ca 2ϩ requirement or the specific activity of -calpain (354,356). Other studies described a heat-stable polypeptide of ϳ40 -45 kDa isolated from human neutrophils (353) or rat skeletal muscle (357) that reduced the Ca 2ϩ concentration required for maximal activity of m-calpain to 20 M or less without affecting its specific activity. The 40-to 45-kDa "activator" also had no effect on the catalytic properties of -calpain.…”
Section: The Ca 2ϩ Requirement Problemmentioning
confidence: 99%
“…Caldonopain assay was conducted after 12 h incuba- [23] or there is a conformational change of the molecule to overcome the effect of this built-in inhibitor is yet to be established. We also propose that due to prolong incubation an appreciable amount of the endogenous inhibitor is possibly digested by the proteolytic enzyme and as a result, loses its inhibitory effect to a great extent.…”
Section: Discussionmentioning
confidence: 99%